반복인출 및 메타인지를 촉진하는 문제기반 학습법이 학생들의 학습에 미치는 효과 - 김시영(Si Yung Kim); 김시현(Si Hyun Kim) (언어치료연구, 2024)
목적: 문제기반 학습은 해결책을 찾아가는 활동 과정에서 학습이 이루어지는 능동적인 학습자 중심 교수 방법이다. 본 연구에서는 반복인출 및 메타인지를 촉진하는 문제기반 학습법을 적용하여 학생들의 학습에 미치는 효과를 살펴보고자 하였다. 방법: 언어치료 전공 학생 52명이 본 연구에 참여하였다. 각 회기는 정답 예측, 출제 의도 예측, 난이도 예측, 점수 예측, 정답 확인, 문제 출제의 6 과정으로 이루어졌다. 본 학습법이 학생들의 학습에 미치는 효과를 살펴보기 위해 자기주도학습역량, 학습몰입 척도, 문제해결력 척도, 자기효능감 척도를 학습법 사전-사후로 비교 분석하였다. SPSS 22.0을 활용하여 대응표본 t-검정을 실시하여 분석하였다. 결과: 첫째, 반복인출 및 메타인지를 촉진하는 문제기반 학습법을 적용한 후에 학생들의 자기주도학습역량은 사전 3.83점에서 사후 4.24점, 학습몰입 척도는 사전 3.67점에서 사후 4.19점, 문제해결력 척도는 사전 3.57점에서 사후 4.08점, 자기효능감 척도는 사전 3.62점에서 사후 4.13점으로 나타났다. 즉, 자기주도학습역량, 학습몰입 척도, 문제해결력 척도, 자기효능감 척도가 모두 유의미하게 향상된 것으로 나타났다. 결론: 반복인출 및 메타인지를 촉진하는 문제기반 학습법이 학생들의 학습에 긍정적인 영향을 미쳤다고 볼 수 있다. 향후 다양한 교과목에 반복인출 및 메타인지 학습법을 적용하여 그 효과를 더욱 확장할 필요가 있다. 또한, 언어치료 전공 학생들의 전공 이해 및 활용에 효과적으로 적용할 수 있는 방안을 모색해야 한다. Purpose: The problem-based learning method is an active learner-centered teaching method in which learning takes place during the course of activities of finding a solution. This study attempted to examine the effects on students’ learning by applying a problem-based learning method that enhances repeated retrieval and meta-cognition. Methods: Fifty-two students majoring in speech-language therapy participated in the study. Each session consisted of six courses: predicting correct answers, predicting question intentions, predicting difficult, predicting scores, checking the answers, and questioning. In order to examine the effects of this learning method on students’ learning, self-directed learning ability, learning engagement, problem-solving ability, and self-efficacy were compared and analyzed before and after the learning method application. A corresponding sample t-test was conducted and analyzed using SPSS 22.0. Results: First, after applying a problem-based learning method that enhances repeated retrieval and meta-cognition, students’ self-directed learning ability score changed 3.83 points to 4.24 points, learning engagement score changed 3.67 points to 4.19 points, problem-solving ability score changed 3.57 points to 4.08 points, and self-efficacy score changed 3.62 points to 4.13 points. In other words, self-directed learning ability, learning engagement, problem-solving ability, and self-efficacy were all significantly improved. Conclusions: The findings support the notion that a problem-based learning method that enhances repeated retrieval and meta-cognition have had a positive effect on students’ learning. Therefore, it is necessary to further expand the effect by applying a learning method including repeated retrieval and meta-cognition to various subjects. In addition, finding ways to effectively apply them to the understanding and utilization of students majoring in speech-language therapy is needed. KCI Citation Count: 0